Avaliação da interação genótipo X ambiente em testes clonais de eucalyptus no estado de Alagoas - Nunes, Tulio dos Santos (2021)
Identifying highly productive genetic materials adapted to different edaphoclimatic conditions is one of the main objectives of evaluating the genotype × environment (G × A) interaction. Thus, the aim of this work was: to select superior Eucalyptus genotypes in wood volume productivity in four locations in the state of Alagoas and to determine the genotype × environment interaction (G×E) using two complementary methods: restricted maximum likelihood/best unbiased linear prediction (REML/BLUP) and GGE biplot (main effects of genotype + genotype × environment interaction) in order to select the best Eucalyptus genotypes for planting on a commercial scale. The tests were installed in four locations in the state of Alagoas (Fazenda Santa Justina, Usina Cachoeira, Usina Capricho and Usina Marituba). The design used was randomized blocks, containing six blocks and nine plants per plot. 40 clones were tested in a spacing of 2.5 m x 2.5 m. At 66 months, survival, mean annual volume increment (MAI) of trees, stem shape, presence of diseases, mortality and failures were evaluated. Genetic parameters were estimated using mixed models (REML/BLUP). For the selection, the genotypic values obtained for the MAI were corrected through its multiplication by the genotypic values obtained for the survival of the genotypes. The top 10 genotypes were selected considering the joint analysis of the environments, individual environments and through the harmonic mean of the genotypic values (MHVG), the relative performance of the genotypic values (PRVG) and the harmonic mean of the relative performance of the genotypic values (MHPRVG). The GGE biplot model was used to identify the ideal genotypes and environments, formation of mega-environments and places with high discrimination and representativeness. Through the genetic parameters it was possible to infer that the G×A interaction found between the environments was of the complex type with the stratification of the environments in two improvement zones. The correction of the productivity by the survival allowed for the obtention of more realistic results for the selection of genotypes. The best genotypes, with a survival rate close to and above 90%, were at the top of the ranking, compared to clones with a low survival rate, but with high individual productivity. The MAI values found for the 10 top clones in the different selection methods were above the national productivity average. The use of the GGE biplot method made it possible to identify the formation of two megaenvironments, in these places it was possible to identify different clones with high productivity. Moreover, this analysis enabled the identification of genetic materials considered ideal and environments that can be used for the selection of superior individuals in the study area, being, therefore, ideal environments, with high discrimination and representativeness for the edaphoclimatic characteristics of the state of Alagoas.